Journals’ guidelines about title, abstract and keywords: An overview of information science and communication science areas - Fujita, Mariângela Spotti Lopes [UNESP] (2018)
Objective: The purpose of this exploratory study was to observe and analyse guidelines for authors on writing their papers’ title, abstract and keywords. Methods: The sample consisted of 64 journals indexed in the Journal Citation Reports (JCR): 32 (50%) Library & Information Science (LIS) journals and 32 (50%) Communication Science (CS) journals. A spreadsheet was used for data collection, containing 36 items grouped into four categories: identification data, guidelines for the title, the abstract, and the keywords of the scientific article. Then, in each category, the LIS journals were compared with CS journals, to verify how specific aspects of knowledge organisation and representation are reflected in editorial policies. Results: Majority of CS journals (27, 84%) and less than a quarter of LIS journals (7, 22%) referred to a style guide on their website. Specific guidelines for the title were presented in 17 (53%) LIS journals and in 23 (72%) of CS journals, mainly concerning the word number. Twenty three (72%) LIS journals and 31 (97%) CS journals included guidelines for writing abstracts, focusing on word number and the structure of abstracts. Instructions for keywords were presented in 21 (66%) LIS journals and 28 (88%) CS journals, defining the number of keywords and the use of controlled vocabulary. Conclusion: There is a tendency to standardise general indications and criteria about titles, abstracts and keywords. Guidelines on writing abstracts, titles and keywords have smaller presence in editorial policies of LIS journals, than of CS journals.